Study of S-band optical amplifiers and its applications / Mohd Zamani Zulkifli - Mohd Zamani, Zulkifli (2012)
Currently, existing networks which utilizes Dense Wavelength Division Multiplexing (DWDM) have come to its limitation, with the increase of data traffic extending the operational bandwidth from the C- to the L-band. Although the L-band can sustain current demands, there is a pressing need to explore the S-band region for future needs. One of the important components for operation in the S-band region is the S-band optical amplifier, which requires in-depth investigation and is the scope and objective of this thesis. The work will undertake a nearly comprehensive evaluation of the different types of optical amplifiers such as Erbium Doped Fibers Amplifiers (EDFAs), Depressed-Cladding Erbium-Doped Fibers Amplifiers (DC-EDFAs), Semiconductor Optical Amplifier (SOAs) and Raman Amplifier (RAs). The methodology of this work is to investigate these amplifiers from the aspect of the gain and noise figure at different input signal wavelengths and powers. Further to this, the optical amplifier is configured into a fiber laser and various parameters such as the tuning range, output power and the Side Mode Supression Ratio (SMSR) will be investigated. Various methods are used to tune the wavelength of the fibre lasers, including the Arrayed Waveguide Gratings (AWGs) and Tunable Bandpass Filters (TBFs) as well as Tunable Fibre Bragg Gratings (TBFGs) for different gain media. Significantly important results were obtained from these investigations, including the generation of an SOA based fiber laser with an ultrawide tuning range of more than 120 nm covering the S-, C- and L- bands. This thesis also presents another application of the S-band amplifier, which is the multi-wavelength Brillouin fiber laser operating in the S-band region. This application is important for the development cost-effective transmission sources for the DWDM systems. The multi-wavelength fiber laser uses the Brillouin effect, which is a non-linear optical effect, together with the EDFA, DC-EDFA, SOA and RA to generate a multi-wavelength output in the S-band region. The developed multi-wavelength Brillouin fiber laser has a number of substantial performance improvements over similar designs, including the number of the Stokes lines generated, flat output peak power and also channel spacing. The studies undertaken and the results obtained in this work can provide important inputs into the design of S-band optical amplifiers for application in future S-band networks. Furthermore, the results obtained in this work are instrumental to the development of tunable S-band fiber laser sources and also multi-wavelength sources for the possibility of usage in DWDM systems.